Green Word in English Lessons - Kerekes Ágnes; Gebula Judit (2004)
In my thesis I will demonstrate how we can connect the English language teaching to environmental education. First I am going to outline the importance of environmental education and protection. Then I am going to write about forest schools where environmental education can take place. In the chapter following it I will focus on the importance of interdisciplinary aspect and on the role that the English language can play. In the last chapter I will present various topics and exercises on this theme.
Keywords: Pedagógusképzés